Modelling the spatial distribution of rainfall-induced landslide susceptibilities in Infanta, Quezon, Philippines (2012)
The municipality of Infanta, Quezon was devastated by landslide and flooding caused by successive typhoons (Unding, Violeta, Winnie and super typhoon Yoyong in 2004. These disasters caused tremendous damages to properties, infrastructure, agriculture and loss of lives in the municipality and nearby towns of Quezon Province. This study was conducted to model the spatial distribution of rainfall-induced landslide susceptibilities in Infanta, Quezon utilizing Geographic Information Systems (GIS).
Keywords: Landslides -- Infanta (Quezon); Geographic Information Systems